The Tarob and the Sacred Oath. Liminal Spirits and Stories Creating Heterotopic Spaces in Dusun Culture - Martin Potter (eTropic: electronic journal of studies in the tropics, 2017)
This article explores two stories told during the production of the transmedia documentary project Big Stories, Small Towns: Bongkud-Namaus in the Dusun villages of Bongkud and Namaus in Sabah, Malaysia. Both stories relate to hungry and sacred entities – an atomised, monstrous moon-eating spirit called the Tarob, and a sacred oath bound in blood, which eats anyone who breaks it. The article will introduce the Big Stories, Small Towns project, the process that underpins this project and the site of production in Sabah of one iteration of the Big Stories, Small Towns, before analysing heterotopic conceptions associated with aspects of folklore in the Southeast Asian region. Providing a theoretical framework that reflects upon a key text by Evans (1953) – an early translator of Dusun folklore for Western audiences – aspects of Dusun culture will be explored that illuminate details of the two case study stories. An historical and theoretical treatment of the stories will frame a fusion of transmedia and folklore in manifesting liminal beings to emergence. This fusion of transmedia and folklore facilitates representation and remediation of cultural identities, thus enabling a wider society – in this case Malaysian society – to develop a more nuanced cultural awareness of itself.